MOTIVATION OF PROFESSIONAL ACTIVITY OF EDUCATORS AND THE HAPPINESS INDEX: AN EMPIRICAL STUDY - Azamjonova Kamola Tukhtamish qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the motivation of educators’ professional activity and the index of subjective happiness. The study is based on psychological and pedagogical approaches and includes an analysis of intrinsic and extrinsic motivation, as well as the relationship between professional satisfaction and the happiness index. The empirical results demonstrate that intrinsic motivation is a key factor in the formation of professional satisfaction and subjective well-being of educators. The socio-psychological environment and institutional support also play an important role in enhancing professional happiness and stress resilience. The findings provide an empirical basis for developing practical recommendations aimed at fostering constructive motivation and increasing professional satisfaction among educators.